2018
DOI: 10.1016/j.algal.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical carbon dioxide extraction and fractionation of lipids from freeze-dried microalgae Nannochloropsis oculata and Chlorella vulgaris

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…For N. oculata cells, our results are in contrast to those by Ryckebosch et al (2014), who reported that standard cultures of the alga contained about 40% of neutral lipids. Hovewer, our data are in agreement with other papers using the alga under stress conditions (Obeid et al 2018). In our experiments, the stress conditions could be the age of culture in mono-cultivation and both the age of the culture and other stresses, like hydrodynamic stress or interaction with mucopolysaccharides released by T. lutea.…”
Section: Lipid and Fatty Acid Profilesupporting
confidence: 92%
“…For N. oculata cells, our results are in contrast to those by Ryckebosch et al (2014), who reported that standard cultures of the alga contained about 40% of neutral lipids. Hovewer, our data are in agreement with other papers using the alga under stress conditions (Obeid et al 2018). In our experiments, the stress conditions could be the age of culture in mono-cultivation and both the age of the culture and other stresses, like hydrodynamic stress or interaction with mucopolysaccharides released by T. lutea.…”
Section: Lipid and Fatty Acid Profilesupporting
confidence: 92%
“…Cell disruption can be achieved by physical (Ultrasonication, High Pressure Homogenization, Bead Milling, Pulsed Electric Field) chemical (Acid, Alkaline and Oxidation), thermal (Hydrothermal, Steam Explosion) and biological methods (Enzymatic treatment) (Soo Youn . During cell wall disruption, intracellular molecules can be extracted with organic solvents (Araujo et al, 2013), ionic liquids (Y. , supercritical CO2 (Reyes et al, 2016;Cheng et al, 2011) or supercritical mixtures of CO2 and solvents (Obeid et al, 2018). Cell-wall components fractionation, may require their further depolymerization via hydrothermal (Lorente et al, 2017), acid (Hernández et al, 2015) or enzymatic hydrolysis (Sierra et al, 2017).…”
Section: Microalgae In the Context Of Biorefinerymentioning
confidence: 99%
“…The most common supercritical solvent is carbon dioxide (104, 105) but acetone, methanol, ethanol, and water also used for lipid extraction under supercritical conditions (103,106). Supercritical carbon-dioxide efficiently solubilize non-polar compounds while the extraction polar compounds can be increased using a polar co-solvent as ethanol, methanol, and acetyl chloride (107) or azeotropic mixtures as hexane/ ethanol (108). The parameters of SFE, such as extraction temperature, extraction time, biomass/solvent ratio, and pressure significantly influence the quality of extracted oil and obtained biodiesel (109,110).…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%